Efeitos cardiovasculares do hipertireoidismo experimental, do treinamento físico e de sua associação em ratos Wistar - Lopes, Leandro Teixeira Paranhos (2010)
Cardiac hypertrophy is a component of cardiac remodeling and involves changes in the geometric structure, composition biochemistry, electrical generation and conduction, the volume of muscle cells, the organization of collagen and blood vessels. Excess thyroid hormone causes cardiac hypertrophy and hemodynamic side effects, but its association with physical exercise remains unclear. This study aimed to examine the cardiovascular responses to experimentally induced hyperthyroidism in physical training and their combination in rats. Thirty eight Wistar rats were randomized to four experimental groups: exercise (E), thyroid hormone and exercise (HTE), thyroid hormone (TH) and control (C). We evaluated the response of heart rate (HR) and blood pressure (BP) before and after intervention in each group and between them. The wet weight of heart and the LV was obtained at the end of the experiment and compared between groups. Also in this phase was evaluated by measuring the transverse diameter of cardiomyocytes and the results also compared between groups. The results showed that HR in group E was lower at rest compared to all groups. The HR decreased in group E and increased in the other groups at the end of the study. There was no change in BP. The diameter of cardiomyocytes increased in groups E, HT and HTE when it was compared to C. We conclude that the thyroid hormone alone or in combination with physical exercise promotes increased heart rate. Physical training was not able to reduce HR in the presence of HT. There was no difference between groups E, HTE and HT.